On Freud's "Neurosis and Psychosis" and "The Loss of Reality in Neurosis and Psychosis" : 100 years later - Freud, Sigmund, 1856-1939.; Freud, Sigmund, 1856-1939.; Legorreta, Gabriela; Bronstein, Catalina (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"On Freud's "Neurosis and Psychosis" and "The Loss of Reality in Neurosis and Psychosis" explores these two key papers on the topics of psychosis and neurosis and their relationship to the unconscious and to reality. The contributors to this book approach these texts from both a historical and a contemporary point of view, highlighting their fundamental contributions and comparing Freud's thoughts with modern psychoanalytic theory. The chapters demonstrate the ongoing richness of Freud's work and his legacy by highlighting new ideas and developments and include both clinical vignettes and theoretical insight. The contributors also raise questions that deserve further study, about the understanding and treatment of psychosis in children, distinctions and similarities between autism and psychosis, and the way in which aspects of our rapidly changing world - social media, climate change, AI - influence the evolution of psychotic states. On Freud's "Neurosis and Psychosis" and "The Loss of Reality in Neurosis and Psychosis" will be essential reading for psychoanalysts and psychoanalytically oriented clinicians in practice and in training. It will also be of interest to academics and scholars of psychoanalytic studies and to readers interested in how modern clinicians interpret Freud's work"--
Keywords: Freud, Sigmund, -- 1856-1939.; Psychoanalysis; Neuroses; Psychoses; PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Mental Health